2014
DOI: 10.3390/molecules19056142
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer Activities of Polyynes from the Root Bark of Oplopanax horridus and Their Acetylated Derivatives

Abstract: Six polyynes OH-1~6, some of which are occur naturally in acetylated form, had been isolated and identified from the root bark of Oplopanax horridus (Devil's Club), a natural dietary supplement and medicinal plant in North America. During the evaluation of the polyynes' potential anticancer activities, sixteen more acetylated derivatives OHR-1~16 have synthesized and their anti-proliferation activity on MCF-7, MDA-MB-231, A549, HepG2 and LO2 cells assayed to elucidate their structure-activity relationships. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Among them, C 17 and C 18 -polyynes were predominantly reported for their anticancer effects [ 55 58 ]. In the tested cancer lines, the antiproliferation effects of polyyne 1 displayed stronger effects than 3 and 5 , while polyyne 2 exhibited greater activities than 4 and 6 [ 48 , 59 ]. Among these polyynes, 1 (FAD) shows the strongest anticancer activity, suggesting that FAD is a candidate for chemical modification [ 60 62 ].…”
Section: Structure-activity Relationship Of Polyynes On Anticancermentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, C 17 and C 18 -polyynes were predominantly reported for their anticancer effects [ 55 58 ]. In the tested cancer lines, the antiproliferation effects of polyyne 1 displayed stronger effects than 3 and 5 , while polyyne 2 exhibited greater activities than 4 and 6 [ 48 , 59 ]. Among these polyynes, 1 (FAD) shows the strongest anticancer activity, suggesting that FAD is a candidate for chemical modification [ 60 62 ].…”
Section: Structure-activity Relationship Of Polyynes On Anticancermentioning
confidence: 99%
“…Regarding the chemical structures of these polyynes, they could be divided into three pairs grouped by their terminal bond moieties, i.e., 1 vs. 2 ; 3 vs. 4 ; and 5 vs. 6 . With regard to their anticancer effects, polyyne 1 , 3 , and 5 showed greater potent activity, suggesting that the terminal ethenyl group improved anticancer activity [ 48 , 59 ]. Recently, it is reported that the pharmacokinetic parameters between 1 and 2 had significant differences.…”
Section: Structure-activity Relationship Of Polyynes On Anticancermentioning
confidence: 99%
See 2 more Smart Citations
“…Primary structure-activity analysis suggested that the terminal ethylenic bonds of polyacetylenes ( Figure 1) would influence their activity while the protection of single hydroxyl group might not influence the inhibitions very much [25,26]. Inspired by these results, we designed the synthetic route of falcarindiol analogues by constructing the first chiral center at the C-8 with an alkyne addition to aldehyde.…”
Section: Resultsmentioning
confidence: 99%